2020
DOI: 10.1007/s00125-020-05279-1
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in first- and second-generation immigrants to Sweden diagnosed with type 2 diabetes: a 10 year nationwide cohort study

Abstract: Aims/hypothesis Non-Western immigrants to Europe are at high risk for type 2 diabetes. In this nationwide study including incident cases of type 2 diabetes, the aim was to compare all-cause mortality (ACM) and cause-specific mortality (CSM) rates in first- and second-generation immigrants with native Swedes. Methods People living in Sweden diagnosed with new-onset pharmacologically treated type 2 diabetes between 2006 and 2012 were identified through the Swedish Prescribed Drug Register. They were followed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
0
13
1
Order By: Relevance
“…We have previously reported that Middle Eastern and non‐western immigrants have an earlier diabetes onset 5 . In our study, we saw differences with a higher incidence and a shorter time until diabetes diagnosis for the Iraqi born group but we could not show that the differences were statistically significant; this was most likely due to lack of power.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…We have previously reported that Middle Eastern and non‐western immigrants have an earlier diabetes onset 5 . In our study, we saw differences with a higher incidence and a shorter time until diabetes diagnosis for the Iraqi born group but we could not show that the differences were statistically significant; this was most likely due to lack of power.…”
Section: Discussioncontrasting
confidence: 75%
“…It is known that migration and urbanisation are risk factors for type 2 diabetes 3 . Previous studies have shown that immigrants from the Middle East have a higher prevalence of type 2 diabetes, and 6–10 years earlier diabetes onset compared to Swedish born individuals 4,5 . Recognising predictors of type 2 diabetes in high‐risk populations is important for identifying proper preventive actions and to decrease the risk of developing type 2 diabetes and its complications.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indicates that migrants develop type 2 diabetes 10-20 years earlier [9][10][11] and at a lower level of BMI [12,13] than Europeans. The United Kingdom (UK) Biobank cohort data, for example, show that, for the equivalent prevalence of diabetes at 30 kg/m 2 in European descent participants, BMI equated to 22.0 kg/m 2 in South Asians, 26.0 kg/m 2 in African descent populations and 24.0 kg/m 2 and 26.0 kg/m 2 , respectively, in Chinese women and Chinese men [12].…”
Section: Type 2 Diabetes Burden In Migrantsmentioning
confidence: 99%
“…By contrast, more recent studies show lower mortality risks in migrants with diabetes compared with Europeans [ 28 ]. In a nationwide 10-year longitudinal study of type 2 diabetes in Sweden, the adjusted risk of all-cause mortality and cause-specific mortality (due to CVD or cancer) was lower in first-generation migrants born in the Middle East, Asia, Africa and Latin America compared with European Swedes [ 11 ]. However, second-generation migrants with type 2 diabetes, especially those with both parents born abroad, had a 28% higher risk of all-cause mortality than the European Swedes [ 11 ].…”
Section: Diabetes-related Complications In Migrantsmentioning
confidence: 99%
See 1 more Smart Citation